A prospective observational study on maternal near miss cases in a rural teaching hospital - Mahajan, Mamta; Soni, Anjali; Sharma, C. D.; Moudgil, Shelley (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Women who have survived complications during pregnancy and child birth have been studied and termed Maternal near miss (MNM). All near misses should be interpreted as free lesson and opportunities to improve the quality of service provision. The aim of the study was to know the incidence, risk factors and underline causes of MNM in our setup as there is limited data from Himachal Pradesh. Methods: The present study was a prospective observational study that was carried out in the department of Obstetrics and Gynecology, Dr. Rajendra Prasad Government Medical College Kangra at Tanda (HP), from 1st January 2018 to 31st December 2018. The patients in this study were, pregnant women who nearly died but survived a complication that occurred during pregnancy, child birth or within 42 days of termination of pregnancy as per WHO MNM criteria 2009. Results: A total of 9690 live births, 5 maternal deaths and 116 MNM cases were reported during the study period. Incidence of MNM observed was 12%. Hypertensive disorders of pregnancy 39.6% cases were most common cause for MNM followed by obstetric hemorrhage 31.03% cases. Majority of neonates i.e.; 58% were admitted to NICU and only 52.7% survived the postnatal complications. Conclusions: Critical analysis of MNM cases will help us in identifying the deficiencies in obstetric care. Maternal mortality and morbidity can be reduced if timely and effective care can be given to women experiencing acute pregnancy related complications. There is need for validation of ‘MNM’ criteria at peripheral levels which will enable them in early identification and timely referral of such cases to tertiary centers.